Manufacture and characterization of kefir made from cow and buffalo milk, using kefir grain and starter culture - Gul, O.; Mortas, M.; Atalar, I.; Dervisoglu, M.; Kahyaoglu, T. (ELSEVIER SCIENCE INC, 2015)
The microbiological and chemical characteristics as well as organic and amino acid profiles of kefir samples made from cow and buffalo milks fermented by kefir grains and starter culture were investigated during storage for 21 d at 4 degrees C. After incubation, lactic, acetic, and citric acid concentrations showed a difference among the samples due to milk type and production methods. Storage time had little effect on the organic acid values of kefir samples. As compared with cow milk kefir, buffalo milk kefir had higher numbers of microorganisms, except lactobacilli, at the end of storage. Whereas pH and titratable acidity exhibited similar changes during storage in all kefir samples, ethanol levels were significantly increased in buffalo milk kefir samples. Glutamic acid was the major amino acid at all sampling times for all samples. Tyrosine, serine, histidine, alanine, methionine, and lysine concentrations were determined to be different in all samples depending on milk type. In general, due to the higher microbial population (especially yeast), kefir made from buffalo milk may be preferred.
Keywords: buffalo milk; cow milk; kefir; characterization; LACTIC-ACID BACTERIA; ORGANIC-ACIDS; FERMENTATION; STORAGE; YEASTS; FAT; Agriculture; Food Science & Technology